Ground receiving station reference pair selection technique for a minimum configuration 3D emitter position estimation multilateration system - Yaro, A.S. (VSB-Technical University of Ostrava, 2017)
Multilateration estimates aircraft position using the Time Difference Of Arrival (TDOA) with a lateration algorithm. The Position Estimation (PE) accuracy of the lateration algorithm depends on several factors which are the TDOA estimation error, the lateration algorithm approach, the number of deployed GRSs and the selection of the GRS reference used for the PE process. Using the minimum number of GRSs for 3D emitter PE, a technique based on the condition number calculation is proposed to select the suitable GRS reference pair for improving the accuracy of the PE using the lateration algorithm. Validation of the proposed technique was performed with the GRSs in the square and triangular GRS configuration. For the selected emitter positions, the result shows that the proposed technique can be used to select the suitable GRS reference pair for the PE process. A unity condition number is achieved for GRS pair most suitable for the PE process. Monte Carlo simulation result, in comparison with the fixed GRS reference pair lateration algorithm, shows a reduction in PE error of at least 70 for both GRS in the square and triangular configuration. © 2017 ADVANCES IN ELECTRICAL AND ELECTRONIC ENGINEERING.